(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Critical thinking is a vital skill for navigating the complexities of today's world. As society confronts growing challenges in politics, technology, and global issues, it is essential for students to learn how to effectively analyze, evaluate, and synthesize information. This article highlights the significance of teaching critical thinking and outlines ways educators can create environments that promote these important skills. By examining strategies such as open-ended questions, debates, real-world scenarios, and reflective practices, the article illustrates how teachers can nurture independent thinkers capable of making informed decisions. Additionally, it addresses the challenges and obstacles to teaching critical thinking and offers solutions to overcome them.